2023
DOI: 10.3390/ijms241713033
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dynamics in Neurodegenerative Diseases: Unraveling the Role of Fusion and Fission Processes

Hubert Grel,
Damian Woznica,
Katarzyna Ratajczak
et al.

Abstract: Neurodegenerative diseases (NDs) are a diverse group of disorders characterized by the progressive degeneration and death of neurons, leading to a range of neurological symptoms. Despite the heterogeneity of these conditions, a common denominator is the implication of mitochondrial dysfunction in their pathogenesis. Mitochondria play a crucial role in creating biomolecules, providing energy through adenosine triphosphate (ATP) generated by oxidative phosphorylation (OXPHOS), and producing reactive oxygen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…Neurodegenerative diseases, such as Parkinson's disease (PD), Alzheimer's disease (AD), Huntington's disease (HD), and Multiple Sclerosis (MS), are age-related chronic wasting diseases characterized by neurodegenerative changes (Grel et al 2023). Although these neurodegenerative diseases differ in pathogenic events, onset, and progression, the presence of dysfunctional mitochondria are common features (Rodolfo et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Neurodegenerative diseases, such as Parkinson's disease (PD), Alzheimer's disease (AD), Huntington's disease (HD), and Multiple Sclerosis (MS), are age-related chronic wasting diseases characterized by neurodegenerative changes (Grel et al 2023). Although these neurodegenerative diseases differ in pathogenic events, onset, and progression, the presence of dysfunctional mitochondria are common features (Rodolfo et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, pathological disturbances resulting in damage to mitochondrial components have the potential to affect the whole mitochondrial compartment, while individual components of the mitochondrial compartment are degraded and recycled as necessary. Mitochondrial fusion-fission processes have been found to be disrupted in several diseases, including neurodegeneration, obesity, type II diabetes, and COVID-19 [75,76]. Disruption in mitochondrial dynamics can cause oxidative stress, mitochondrial disfunction and dysregulation of the innate immune response during infection by SARS-CoV-2.…”
Section: Mitochondrial Fusion and Fissionmentioning
confidence: 99%
“…They regulate cell biology by maintaining the balance of ROS and calcium homeostasis [10][11][12] . Numerous studies have indicated a strong correlation between mitochondrial dysfunction and the development of various diseases [13][14][15] . Therefore, investigating mitochondrial function may provide new insights for the treatment of CP.…”
Section: Introductionmentioning
confidence: 99%